Antibacterial Activity and Thin-Layer Chromatography (KLT) Ethanol Extract of Dragon Scale Leaves (Drymoglossum piloselloides (L.) C. Presl) Against Bacteria Staphylococcus epidermidis - Syahputri, Hindri; Pertiwi, Nia Novranda; Sari, Syilvi Rinda; Simanjuntak, Monica Nelly; Sari, Melia; Andry, Muhammad; Nasution, Muhammad Amin; Rezaldi, Firman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The dragon scale plant is a plant containing flavonoid compounds, tannins, alkaloids, saponins. Flavanoid compounds, alkaloids, and tannins are found in dragon scales that are thought to provide antibacterial effects. Thin Layer Chromatography Test (KLT). On quarstin there is a stain distance spot of 1 cm and an 8 cm motion phase with an Rf value of 0.129 and in the extract there is a stain spot of 7.3 cm with an 8 cm motion phase with an Rf value of 0.9. In Staphylococcus epidermidis bacteria from the average of the largest inhibitory zones are applied to the extract with a concentration of 20%. The diameter of the average inhibitory zone formed around the disc paper at each concentration is: 5% 10.5 mm ± 0.20 at a concentration of 10% 11.26 mm ± 0.20 and a concentration of 20% 12.2 mm ± 0.30 each concentration has a strongly categorized response. Ethanol extract of dragon scale leaves (Drymoglossum piloselloides (L.) C. Presl) has antibacterial activity against Staphylococcus epidermidis. The diameter of the inhibitory zone that is best formed in the treatment of dragon scale leaf ethanol extract against Staphylococcus epidermidis bacteria with a concentration of 20%12.2 mm±0.30 is 12.2 mm with a strong category.